Development of Android-based learning media using Smart Apps Creator on high school trigonometry material - Dita Kirana; Rahmi Rahmi; Mulia Suryani (Universitas Sarjanawiyata Tamansiswa, 2023)
This research is motivated by students' low enthusiasm to participate in mathematics. Students are more interested in using technological developments in learning because they look attractive, simple, and practical. This research aims to produce learning media based on Android using a valid and practical Smart Apps Creator. This research type is often known as Research and Development (R&D) using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The participants in this study were XI IPA students at SMAN 1 X Koto in the Tanah Datar region. Validation questionnaires and practicality test questionnaires were the instruments utilized in this investigation. The percentage of the final assessment of the validity of learning media was 92.5%, with a very valid category based on the findings of the validator's assessment, which included media specialists and material experts. The teacher received a total score of 100% in the extremely practical area for the practicality rating. The pupils' ultimate practicality score fell into the very practical group with an 83.24% percentage. With a typical rate of 91.6%, using media is feasible. Based on the study's findings, the Smart Apps Creator-based Android learning resources for class XI IPA SMAN 1 X Koto, Tanah Datar Regency have been deemed legitimate and workable for usage by instructors and students.